ATTRIBUTES OF AN EFFECTIVE NURSING TEACHER: A CROSS-SECTIONAL STUDY - Jokhio, Pir Bux; Panhwar, Ghulam Abbas; Burdi, Rashid Hussain; Shar, Bhagul; Bibi, Musrat; Kunmbhar, Muhammad Iqbal (Annals of Allied Health Sciences, 2023)
Objective: To identify characteristics/attributes of a quality nursing teacher using survey instrument: attributes of quality health educator’. Material & Methods: This is a cross-sectional study conducted at Begum Bilqees Sultana, Institute of Nursing, Peoples University of Medical & Health Sciences, Shaheed Benazirabad during January-March, 2022. A structured 15-item, ranking-based ’Survey instrument: attributes of an effective health educator scale’ was used to collect the data from four-year Bachelor’ of Science in Nursing students of study year 2nd, 3rd, & 4th year. First-year students were excluded because of their less than 06 months of educational experience. Results: Participants ranked clarity, knowledge base, well-prepared, respects students’ autonomy & independence, and enthusiastic attributes at 1st m 2nd, 3rd, 4th, & 5th slot, respectively. The 6th, 7th, 8th, 9th, & 10th priority positions were by ‘grabbed feedback, organization skills, listening skills & availability, role model, and sincerity’ as teachers’ attributes. The scholarly activity and utilization of evidence-based practice attributes failed to gain students’ due attention. Conclusion: The failure of students to provide scholarly activity and utilization of evidence-based practice attributes is another area for future research. In-depth studies are warranted to drill the factors that inhibit students’ due attention in this regard.